Fairy godmother - Lackey, Mercedes (New York Luna, 2004)
In the mystical realm of the Five Hundred Kingdoms, the newest Fairy Godmother tries to help three impossible princes find the women of their dreams, while fending off an evil sorcerer who is determined to destroy her kingdom.
"A tale of the 500 kingdoms"--Cover.
Includes question and answer with author (p. [480]-481).
99555
Keywords: Donkeys Fiction; Kings, queens, rulers, etc; History Fiction; Great Britain -- History; Fantasy fiction; Historical romance